Impact of Leadership Style to the Business Performance: Balanced Scorecard Approach - Ivan Miloloža (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
Leadership in modern business plays a crucial role in the business success of companies. Previous studies were focused mainly on measurement of financial performance management. The aim of this paper is to explore the extent to which leadership styles affect the success of the company using the system of balanced scorecard approach. A survey was conducted on a sample of Croatian companies, and Leadership Style Questionnaire has been used. The results showed that autocratic leadership has mostly negative impact on process efficiency and knowledge and employees management. Democratic leadership has mostly positive impact on all aspects of efficiency measured by a system of balanced scorecard approach. Laissez-faire leadership has significantly less impact on the efficiency then the other leadership styles.
Keywords: M1; 330; leadership; balance scorecard; autocratic; democratic; laissez-faire; knowledge management; finance; markets; processes